Leverage adjustment after mergers and acquisitions - Khoo, J.; Durand, Robert; Rath, S. (Blackwell Publishing, 2015)
© 2015 AFAANZ. Australian firms have leverage targets. Speeds of adjustment to a target capital structure are higher than previously published estimates when there are major disruptions to firms' leverage ratios. Firms exploit company-specific characteristics to achieve these targets. Profitability and cash levels are important drivers of the speeds of adjustment. Firms, which have lower profitability or higher cash levels, appear to adjust faster.